Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.3861
|View full text |Cite
|
Sign up to set email alerts
|

AB0434 Tofacitinib in rheumatoid arthritis: real life experience

Abstract: BackgroundTofacitinib is a new small molecule, Janus kinase 1 and 3 inhibitor, interfering with the JAK-STAT signaling pathway. The JAK-STAT transmits the extracellular information in the cell nucleus, influencing DNA transcription. Its efficacy and safety in Rheumatoid Arthritis (RA) has been demonstrated in different phase II, III and long-term clinical studies. It has been approved in Argentina for the treatment of patients with moderate to severe rheumatoid arthritis RA with failure to conventional DMARDs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The percentage of patients in our study who discontinued TOFA due to adverse events was 9.3% (46/493), which is similar to that reported in most of the literature (3.2%–9.6%) 10 31–35. However, some studies have shown a higher percentage of discontinuation due to adverse events 36 37.…”
Section: Discussionsupporting
confidence: 87%
“…The percentage of patients in our study who discontinued TOFA due to adverse events was 9.3% (46/493), which is similar to that reported in most of the literature (3.2%–9.6%) 10 31–35. However, some studies have shown a higher percentage of discontinuation due to adverse events 36 37.…”
Section: Discussionsupporting
confidence: 87%
“…In the absence of information on the causes of discontinuing the medications, we could not provide further explanation for this observation. Previous cohort studies reported discontinuation due to adverse events in 3.2-24.3% of the patients who were followed for 6-22 months (37,(40)(41)(42)(43)(44)(45). In those studies, 1.6-20.8% of tofacitinib users discontinued their treatment due to a lack/loss of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Unlike the US registry, the RWS evidence of TOF monotherapy in LatAm shows results equal to or even lower than our cohort (10-41%). [19][20][21] Difference between US data and LatAm data could be the source of information to evaluate results (claims data versus medical records).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] In LatAm particularly, there are almost no data available. [19][20][21] We therefore decided to assess the effectiveness, safety and drug survival of TOF in RA patients from Argentina. Additionally, baseline predictive factors for TOF response were studied.…”
Section: Introductionmentioning
confidence: 99%